Monensin Sensitive 1 Regulates Dendritic Arborization in Drosophila by Modulating Endocytic Flux - Harish, Rohit Krishnan; Tendulkar, Shweta; Deivasigamani, Senthilkumar; Ratnaparkhi, Anuradha; Ratnaparkhi, Girish S. (Frontiers in Cell and Developmental Biology, 2019)
Monensin Sensitive 1 (Mon1) is a component of the Mon1:Ccz1 complex that mediates Rab5 to Rab7 conversion in eukaryotic cells by serving as a guanine nucleotide exchange factor for Rab7 during vesicular trafficking. We find that Mon1 activity modulates the complexity of Class IV dendritic arborization (Da) neurons during larval development. Loss of Mon1 function leads to an increase in arborization, while increased expression, leads to reduced arborization. Mon1 activity also affects dendritic tiling and self-avoidance in the same neurons. The ability of Mon1 to influence dendritic development is possibly a function of its ability to affect Rab family GTPases that are central players in vesicular trafficking. Earlier, these GTPases, specifically Rab1, Rab5, Rab10 and Rab 11 have been shown to regulate dendritic arborization. We have conducted genetic epistasis experiments, by modulating the activity of Rab 5, Rab 7 and Rab 11 in Da neurons, in Mon1 mutants and demonstrate that the ability of Mon1 to regulate arborization is possibly due to its effect on the recycling pathway rather than the degradative pathway. Dendritic branching is critical for proper connectivity and physiological function of the neuron. An understanding of regulating elements, such as Mon1, as demonstrated by our study, that regulate this process is essential to understand neuronal function.